Single-cell RNA Sequencing of Cardiomyocytes in Early Ischemic Heart Disease - Rauf, Qasim; Zahra, Atya; Saeed, Hadi Yousuf; Kumar, Sanjay; Ahmed, Hamdy Abdelfattah; Akhtar, Waqas; Saleem, Satwat (Journal of Neonatal Surgery, 2024)
Background: To explore the transcriptional profile of cardiomyocytes in early IHD using single-cell RNA sequencing (scRNA-seq), with a focus on stress-response, hypoxia-related, and contractility-associated genes. Methods: This descriptive study included myocardial tissue samples from 72 individuals with clinically confirmed early IHD, collected between August 2023 to August 2024. Single-cell suspensions were prepared and sequenced using the 10x Genomics platform. Differential gene expression and pathway enrichment analyses were conducted to identify key molecular signatures. Results: The analysis revealed distinct transcriptional changes, including upregulation of NPPB, HIF1A, and DDIT3, indicating stress and hypoxia responses. Meanwhile, structural genes such as MYH6 and TNNT2 were significantly downregulated. Pathway analysis highlighted activation of apoptotic and inflammatory processes, along with suppression of oxidative phosphorylation. Conclusion: Cardiomyocytes exposed to early ischemia demonstrate a shift in gene expression toward stress adaptation, hypoxic signaling, and diminished contractile function. These early molecular patterns, captured at single-cell resolution, may serve as potential biomarkers or therapeutic targets in the prevention of myocardial progression.